Challenges in implementing the management of conservation units: an analysis of UCs in the state of Paraíba (PerCursos, 2025)
This article analyzes the challenges to the effective management of Conservation Units (CUs) in the state of Paraíba, based on the guidelines established by Law No. 9.985/2000, which instituted the National System of Nature Conservation Units (SNUC), and Decree No. 4.340/2002, which regulates it. The study adopts a case study methodology, focusing on a Strictly Protected Conservation Unit that was decommissioned (or disestablished / deregistered) due to the absence of effective governance. By legal definition, CUs are territorial spaces with relevant natural resources, established by the government for conservation purposes and subject to a special administrative regime. The research involved bibliometric and documentary analysis, fieldwork, and interviews with environmental managers. The results reveal significant institutional fragility: of the 33 CUs located in Paraíba, approximately 73% lack a management council, and around 82% are without a management plan. These findings underscore the urgency of reassessing management strategies and strengthening the enforcement of the legal framework established by the SNUC.
Keywords: conservation units; management; decommissioning; park